Pyrolysis Process of Fatty Acid Methyl Ester (FAME) Conversion into Biodiesel - Bambang Irawan; Rusdianasari; Abu Hasan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
Biodiesel is a biomass fuel that can replace petroleum diesel fuel. One of the advantages of biodiesel fuel as renewable energy source that it is more environmentally friendly than fossil fuels because biodiesel significantly reduces greenhouse gas emissions compared to fossil fuels. FAME (fatty acid methyl ester) is a derivative product of CPO (crude palm oil) that has been treated both physically and chemically. The main advantage of FAME lies in the low content of impurities, especially sulphure and metal content. FAME comes from vegetable oil raw materials, which contain high enough fatty acids, around 61-62%, and nowadays, it is used as a mixture with petroleum diesel. The characteristics of biodiesel obtained from the conversion of FAME into biodiesel by pyrolysis at a temperature range of 160 – 200 oC indicate that the biodiesel produced is density 0.8475 kg/m3, viscosity 3.053 cSt, calculated cetane index (CCI) 48.5, flash point 59oC, moisture content 223 ppm, and sulphure content of 0.07% m/m. The results obtained are below the maximum limit of the specified biodiesel quality requirements.